Analisis Kerusakan Track Adjuster Excavator Hitachi ZX 200 Di PT. Pelabuhan Tanjung Priok Cabang Banten - Al Fikri Muhamad Ramdani; Ananda Yhuto Wibisono Putra (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This research aims to analyze the causes of damage to the track adjuster of the Hitachi ZX 200 excavator operating at PT Pelabuhan Tanjung Priok Branch Banten. The track adjuster functions to maintain track tension so that the stability and mobility of the excavator remain optimal during operations. This study employs a qualitative approach with a case study method, while the data collection techniques include observation, interviews, and component disassembly to identify damage in detail. The results show that the most frequent damage occurs in the adjuster seal, which causes hydraulic oil leakage and weakening of the recoil spring. The main contributing factors include operation in harsh terrains, component lifespan exceeding service limits, and suboptimal periodic maintenance. The impact is highly significant as it disrupts the excavator’s performance and slows down the loading and unloading process at the port. Therefore, proactive maintenance strategies such as Reliability Centered Maintenance (RCM) and timely component replacement